Clinical features of type 1 and 2 refractory celiac disease: Results from a large cohort over a decade. Issue 2 (February 2023) - Elli, Luca; Soru, Pietro; Roncoroni, Leda; Rossi, Francesca Gaia; Ferla, Valeria; Baldini, Luca; Nandi, Nicoletta; Scaramella, Lucia; Scricciolo, Alice; Rimondi, Alessandro; Fusco, Nicola; Croci, Giorgio Alberto; et al.
Abstract: Objectives: Refractory celiac disease (RCeD) is a rare complication of celiac disease (CeD) with a severe prognosis. We describe a cohort of patients with RCeD, their clinical and histological features at diagnosis, after therapy and at lymphoma onset, and the rate and causes of death over a 17-year follow-up. Methods: We retrospectively enrolled RCeD-I and RCeD-II patients attending our center between January 2002 and October 2019. Medical data were collected at diagnosis and during monitoring. Response to therapy, changes in RCeD molecular markers, number of hospitalizations, discharge diagnosis, and cause and date of death were evaluated. The control cohort consisted of 1015 responsive CeD patients. Results: Compared with RCeD-I, RCeD-II more frequently exhibits diarrhea (83 vs 64%), anemia (61 vs 50%), hypoalbuminemia (70 vs 21%), parenteral nutrition need (48 vs 7%), ulcerative jejuno-ileitis (7 vs 39%), and extended small intestinal atrophy (62 vs 21%). One RCeD-I and six RCeD-II patients developed lymphoma. Ten RCeD-II patients died, four from lymphoma progression. Among RCeD-II patients, atrophy extension was the only parameter correlated with hypoalbuminemia and mortality. Conclusions: Clinical severity, response to therapy, and mortality differ between RCeD-I and RCeD-II. Atrophy extension, evaluated at capsule endoscopy, was associated with disease severity and mortality.